Distortion-rate functions for quantized compressive sensing - Wei Dai; Hoa Vinh Pham; Milenkovic, O. (2009 IEEE Information Theory Workshop on Networking and Information Theory, 2009)
We study the average distortion introduced by quantizing compressive sensing measurements. Both uniform quantization and non-uniform quantization are considered. The asymptotic distortion-rate functions are obtained when the measurement matrix belongs to certain random matrix ensembles. Furthermore, we adapt two well-known compressive sensing reconstruction algorithms to accommodate the quantization effects. The performance of the new reconstruction methods is assessed through extensive computer simulations.